Observations on a method of recording of bronchial tone (Revista Española de Fisiología, 1948)
The possibilities of registering the bronquial calibre by means of a system of artificial breating is studied experimentally in dogs. The results obtained lead to the conclusion that the graphic is influenced by bronchial as well as vascular effects. Therefore tris type of method is little adecuate for the registering of the bronchial tone in ordinary phisiological conditions.